REEXAMINING THE QUANTITY THEORY OF MONEY: AN EMPIRICAL ANALYSIS FROM THE JOINT HYPOTHESIS - Cheng-Wen Lee; Andrian Dolfriandra Huruta (Economic Review)
The joint hypothesis test is a replicable interpretation of the quantity theory of money (QTM) when used as an inflation theory. This study examined the effect of money supply and gross domestic product (GDP) growth on inflation volatility. We used the cross-country data of 40 countries, both in 2002 and 2014, from the World Bank publications. We analyzed the data using both the unrestricted regression model and joint hypothesis testing (the Wald test). The unrestricted regression results pointed inflation volatility in 40 countries was mostly driven by the monetary side, not by the real sector. Meanwhile, the joint hypothesis test demonstrated Strong Wald and Weak Wald test for the QTM prediction were rejected. These findings implied undesirable results from a monetarist perspective. We proposed an alternative method to confirm the joint hypothesis test from the QTM. It would be interesting to see whether our findings hold in other countries.